2021
DOI: 10.1038/s41598-021-00938-8
|View full text |Cite
|
Sign up to set email alerts
|

Combining genetic risk score with artificial neural network to predict the efficacy of folic acid therapy to hyperhomocysteinemia

Abstract: Artificial neural network (ANN) is the main tool to dig data and was inspired by the human brain and nervous system. Several studies clarified its application in medicine. However, none has applied ANN to predict the efficacy of folic acid treatment to Hyperhomocysteinemia (HHcy). The efficacy has been proved to associate with both genetic and environmental factors while previous studies just focused on the latter one. The explained variance genetic risk score (EV-GRS) had better power and could represent the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Inflammatory Bowel Disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), is a group of disorders involving alterations in gastrointestinal physiology and chronic inflammation of the mucous membranes (Gampierakis et al, 2021;Lohning et al, 2021) Previous studies have confirmed that HHcy is a risk factor associated with cardiovascular disease and possibly an important independent risk factor for inflammatory bowel disease (Vezzoli et al, 2020;Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory Bowel Disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), is a group of disorders involving alterations in gastrointestinal physiology and chronic inflammation of the mucous membranes (Gampierakis et al, 2021;Lohning et al, 2021) Previous studies have confirmed that HHcy is a risk factor associated with cardiovascular disease and possibly an important independent risk factor for inflammatory bowel disease (Vezzoli et al, 2020;Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%